CiteSpace에 기반한 중국 대운하 문화상품 디자인 특성 및 트렌드 분석 연구 - 류익염(Yi Ran Liu); 정원준(Won-Jun Chung) (한국디자인리서치, 2024)
본 논문에서는 중국 대운하 문화상품 디자인 분야의 연구 현황과 동향을 분석하고 논술하고자 한다. 연구자는 2014년부터 2024년까지 중국 국가지식기반시설(CNKI) 데이터베이스에서 관련 문헌을 검색 및 선별하고, CiteSpace 소프트웨어를 사용하여 선별한 문헌에 대해 정량적 분석과 지식 지도 구축을 진행하였다. 본 연구의 목적은 대운하 문화상품 디자인 분야의 이슈와 최근 동향을 파악히고 향후 발전 가능한 방향을 모색하고자 하였다. 연구 과정에서 키워드 분석과 저자 협업, 그리고 매커니즘 분포 분석을 통해 관련 분야의 연구 동향과 협업 네트워크에 관한 심층적인 탐색을 진행하였는데 연구 결과, 2014년 이후 대운하 문화상품 디자인에 관한 연구가 점진적으로 증가했지만 전반적으로 아직 탐색 단계에 머물러 있으며, 연구자 간 협력이 잘 이루어지지 않고 상대적으로 분산되어 있었다. 따라서 대운하 문화상품 디자인 분야의 미래 발전 방향은 학제 간 융합과 지역 문화 창의성을 결합하여 지속 가능한 발전을 촉진하는 방향으로 나아가야 한다는 전망을 제시하고자 한다. This study will analyze the current state and trends in the field of the China Grand Canal cultural product design. By screening relevant literature from the CNKI database between 2014 and 2024, the study employs CiteSpace software to conduct bibliometric analysis and construct knowledge maps. The aim of this research is to uncover the key issues and emerging trends in the field of Grand Canal cultural product design, and to explore possible directions for its future development. Through co-occurrence analysis of keywords, analysis of author collaboration, and distribution of institutions, the study delves into the research dynamics and collaboration networks in this field. The findings suggest that although research on Grand Canal cultural product design has gradually increased since 2014, it remains largely exploratory, with relatively dispersed collaboration among researchers. Future development is likely to focus on interdisciplinary integration and the combination of regional cultural creativity to promote sustained progress in this field. KCI Citation Count: 0